(3faMGJ GdRgQ aj Phb Cgd GdYUQs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO, agPG JYdjb SejJg faMGJ GdRgQ aj Phb Cgd GdYUQ, SCdfj aj LeYg UGMHfG HgGA GdOjf Hf SGde GdTGaYj s
(3BNQgG (B:s
(3aHdZ GdSdWGf gPg GdhGbYI, aQb dg hCYGOg HYO eOI bGFdkG dg(B: (3hgd WdGhI aj GdYRd GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfj YTQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B161 s
Keywords: (3GdCOHs